Effect of flaxseed powder supplementation on haematological and serum biochemical profiles of Giriraja birds - Paresh Botle; BG Desai; Shalu Kumar; JS Dhekale; NN Prasade; Abhijeet Joshi (Journal of Livestock Biodiversity, 2025)
The experiment was conducted at Department of Animal Husbandry and Dairy Science, Dr. B.S. Konkan Krishi Vidyapeeth, Dapoli, Dist. Ratnagiri, Maharashtra to determine flaxseed powder supplementation on the haemato-biochemical parameters of Giriraja birds. A total of 140 one-day-old Giriraja chicks were individually weighed and randomly assigned to five treatments, each with 4 replicate pens of 28 chicks. The dietary treatments included were T0: Control (basal ration), T1: basal ration + 2 per cent flaxseed powder, T2: basal ration + 3 per cent flaxseed powder, T3: basal ration + 4 per cent flaxseed powder and T4: basal ration + 5 per cent flaxseed powder. The results of the experiment revealed that incorporation of 5 per cent flaxseed powder in Giriraja bird as feed additive significantly improved haemtological parameters viz. Hb (8.60 mg/dl), RBC (2.501 106/mm3), WBC (22165.5cell/mm3) and PCV (32.35 %) and biochemical traits i.e.Cholesterol (93.92 mg/dl),HDL (53.50 mg/dl), LDL (42.57 mg/dl), VLDL (19.11 mg/dl) and Triglycerides (95.50 mg/dl) as compared with control group. The study concluded that 5.0 per cent of flaxseed powder more beneficial for maintaining blood haematological and serum Biochemical profile. Therefore, it may be recommended that incorporation of flaxseed powder in the basal diet of Giriraja birds improved their physiological status.